LIGHT CURING UNITS AND THEIR INTENSITY OUTPUT IN DENTAL SETUPS OF ISLAMABAD AND RAWALPINDI - Ashfaq, Ahmed Usman; Faridi, Muhammad Ali; Bhatti, Usman Anwer; Khabeer, Abdul (Journal of Ayub Medical College Abbottabad, 2021)
Background: Dental composites are commonly used to restore teeth. However, to ensure adequate physical properties and biocompatibility, they require sufficient light intensity with the help of light curing units (LCU). This study aimed to evaluate the type and intensity of LCU being used in the dental setups of Rawalpindi and Islamabad. Methods: Dental clinics were visited and the type of the LCU was noted. Three consecutive intensity measurements were taken using a radiometer. For Quartz tungsten halogen (QTH) LCU, a light intensity below 300mW/cm2 was considered unsatisfactory, while for light-emitting diode (LED) LCU, a reading below 600mW/cm2 was considered unsatisfactory. To analyse the difference between the output intensities of the two LCU, Mann-Whitney U test was used (p<0.05), while Fisher’s Exact test was used for the association between the type of LCU and clinical acceptability of output intensity. Results: A total of 96 LCU were evaluated, out of which, eight were QTH and 88 were LED. A total of 16.7% LCU were considered unsatisfactory. Amongst them, 62.5% QTH had intensity less than 300mW/cm2, while for LED, 12.5% had intensity below 600mW/cm2. The mean intensity for LED was statistically significant compared to QTH LCU (p<0.05). A statistically significant association existed between the type of LCU and their intensity (p<0.05). Conclusion: A trend towards the use of LED LCU in the dental setups of Islamabad and Rawalpindi was observed. LED LCU showed greater mean light intensity than QTH LCU. Periodic evaluation of LCU using radiometers is suggested to ensure optimal intensity output.